Impact of Pelvic Muscle Exercises on Productive Women’s Health: A Systematic Review - Duong, Linh Thuy; Kustriyani, Menik (University of Muhammadiyah Semarang, 2023)
Pelvic muscle exercises (PMEs), often referred to as Kegel exercises, are a non-invasive intervention aimed at strengthening the pelvic floor muscles, which play a crucial role in various aspects of women’s reproductive and sexual health. This systematic review evaluates the impact of PMEs on the health of productive women, specifically focusing on the prevention and treatment of urinary incontinence, improvement of sexual function, and overall quality of life. A comprehensive literature search identified 20 studies that met the inclusion criteria. The review suggests that PMEs are effective in improving pelvic floor muscle strength, reducing the incidence and severity of urinary incontinence, enhancing sexual satisfaction, and improving quality of life in productive women. However, further research is needed to standardize PME protocols and assess their long-term benefits